Genetically fused T4L acts as a shield in covalent enzyme immobilisation enhancing the rescued activity - Planchestainer, Matteo; Padrosa, David Roura; Contente, Martina Letizia; Paradisi, Francesca (MDPI, 2018)
Enzyme immobilisation is a common strategy to increase enzymes resistance and reusability in a variety of excellent ‘green’ applications. However, the interaction with the solid support often leads to diminished specific activity, especially when non-specific covalent binding to the carrier takes place which affects the delicate architecture of the enzyme. Here we developed a broadly applicable strategy where the T4-lysozyme (T4L) is genetically fused at the N-terminus of different enzymes and used as inert protein spacer which directly attaches to the carrier preventing shape distortion of the catalyst. Halomonas elongata aminotransferase (HEWT), Bacillus subtilis engineered esterase (BS2m), and horse liver alcohol dehydrogenase (HLADH) were used as model enzymes to elucidate the benefits of the spacer. While HEWT and HLADH activity and expression were diminished by the fused T4L, both enzymes retained almost quantitative activity after immobilisation. In the case of BS2m, the protective effect of the T4L effectively was important and led to up to 10-fold improvement in the rescued activity